O sodobnih geopolimernih betonih in projektiranju iz njih grajenih gradbenih konstrukcij - Češarek, Peter (Gradbeni vestnik, 2023)
Modern geopolymer concrete is a composite of sand, aggregate and geopolymer binder, the latter being the product of natural polymerization, in which an aluminosilicatic material (precursor) polymerizes through interaction with an alkaline medium (activator). Various industrial by-products are used as precursors, e.g. slag, fly ash and metakaolin. Thus, geopolimeric concrete exhibits favourable properties in terms of its environmental footprint compared to conventional Portland cement concrete. At the same time, as explained in the first part of the paper, geopolimeric concrete also exhibits other favourable properties, the most important among characteristics of hardened concrete being better resistance to various aggressive environmental influences, better resistance to high temperatures, and some advantages in terms of mechanical (?-?) response. The general shape of the ?-? curves is similar to conventional concretes, which leads us to the conclusion that in the design of a geopolymer concrete structure one could resort to procedures from the field of conventional concretes. However, there are also some obvious differences, due to which these procedures will need to be modified to some extent in advance. The second part of the paper offers a brief insight into the need for such a modification.
Keywords: ?-? curve; ?-? krivulja; analiza plastičnih členkov; geopolimerni beton; geopolymer concrete; mechanical response; mehanski odziv; plastic hinge analysis; post-critical load-bearing structural capacity; postkritična nosilnost konstrukcije